Fresno County Bar Associations' 105th Annual Bar Banquet - Watkins, Howard::::::::: (1987)
1988 Fresno County Bar Association President Herbert Levy speaking at the lectern Sam Palmer, Peter Morris, Fresno County Young Lawyers Association President Brad Hill and Leonard Meyers seated at headtable